Turán inequalities for symmetric orthogonal polynomials - Joaquin Bustoz; Mourad E. H. Ismail (International Journal of Mathematics and Mathematical Sciences)
A method is outlined to express a Turán determinant of solutions of a three term recurrence relation as a weighted sum of squares. This method is shown to imply the positivity of Turán determinants of symmetric Pollaczek polynomials, Lommel polynomials and q-Bessel functions.